2016
DOI: 10.3758/s13415-016-0427-2
|View full text |Cite
|
Sign up to set email alerts
|

Task-related functional connectivity of the caudate mediates the association between trait mindfulness and implicit learning in older adults

Abstract: Accumulating evidence shows a positive relationship between mindfulness and explicit cognitive functioning, i.e., that which occurs with conscious intent and awareness. However, recent evidence suggests that there may be a negative relationship between mindfulness and implicit types of learning, or those that occur without conscious awareness or intent. Here we examined the neural mechanisms underlying the recently reported negative relationship between dispositional mindfulness and implicit probabilistic sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
3
4
0
Order By: Relevance
“…Of note, no participant was able to accurately identify relationships between the cues and targets, supporting the notion that the associations were learned without awareness and were not the result of different explicit learning strategies between younger and older adults. Although the learning and age effects were largely consistent with previous studies using the TLT (Howard et al, 2013(Howard et al, , 2008Seaman et al, 2013;Simon et al, 2012;Stillman et al, 2016aStillman et al, , 2016b and other IAL tasks (Aizenstein et al, 2006;Bennett et al, 2007;Curran, 1997;Fera et al, 2005;Howard et al, 2004), we did not find that the age group difference in the triplet type effect was larger during late learning, as others have (Howard et al, 2008;Simon et al, 2012). This is likely due to methodological differences with the current TLT version that may have facilitated learning in both age groups (e.g., manipulating joint but not conditional probability, using fewer unique triplets to equate the number of HF and LF trials; see Franco et al, 2020) or differences in the definition of early versus late stages from previous studies (e.g., number of exposures to each triplet, number of unique triplets, length of presentation; Rieckmann et al, 2010;Simon et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Of note, no participant was able to accurately identify relationships between the cues and targets, supporting the notion that the associations were learned without awareness and were not the result of different explicit learning strategies between younger and older adults. Although the learning and age effects were largely consistent with previous studies using the TLT (Howard et al, 2013(Howard et al, , 2008Seaman et al, 2013;Simon et al, 2012;Stillman et al, 2016aStillman et al, , 2016b and other IAL tasks (Aizenstein et al, 2006;Bennett et al, 2007;Curran, 1997;Fera et al, 2005;Howard et al, 2004), we did not find that the age group difference in the triplet type effect was larger during late learning, as others have (Howard et al, 2008;Simon et al, 2012). This is likely due to methodological differences with the current TLT version that may have facilitated learning in both age groups (e.g., manipulating joint but not conditional probability, using fewer unique triplets to equate the number of HF and LF trials; see Franco et al, 2020) or differences in the definition of early versus late stages from previous studies (e.g., number of exposures to each triplet, number of unique triplets, length of presentation; Rieckmann et al, 2010;Simon et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…The current study extends prior work by examining the inter-region correlations as a function of both learning stage and age group, as well as assessing the mediating role of prefrontal cortex. Earlier studies have reported similar positive relationships between IALrelated activity in the medial temporal cortex (extending beyond hippocampus) and basal ganglia (caudate) in younger and older adults using functional connectivity analyses of fMRI data acquired during TLT performance (Stillman et al, 2016b) and between the hippocampus and basal ganglia (caudate, putamen, nucleus accumbens) in younger adults using task-related fMRI during other associative learning tasks Stark, 2015, 2011). Converging results across these paradigms provides confidence that the interactions among these regions are reflective of associative learning processes rather than minor task idiosyncrasies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In the laboratory, behavioral evidence of implicit associative learning (IAL) is seen as faster and/or more accurate responses to stimuli that can be predicted based on their relationship to prior events, such as frequently occurring cue-cue-target associations in the Triplet Learning Task (TLT; Howard et al, 2008). IAL has been established in adults across the lifespan, albeit with smaller learning effects in younger-old (65-85 years) relative to young (20-30 years) adults (Bennett et al, 2007;Curran, 1997;Howard et al, 2013Howard et al, , 2008Howard et al, , 2004Seaman et al, 2013;Simon et al, 2012;Stillman et al, 2016aStillman et al, , 2016c. But IAL has not yet been demonstrated in oldest-old adults (90+ years) in spite of extensive characterization of their impairments across other cognitive domains (Melikyan et al, 2019).…”
Section: White Matter Microstructural Correlates Of Associative Learn...mentioning
confidence: 99%